Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

What is the solution to this equation?

[tex]\[ 3(n-9)-2(n+4)=6n \][/tex]

[tex]\( n = \square \)[/tex]


Sagot :

Let's solve the equation step-by-step.

Given:
[tex]\[ 3(n-9) - 2(n+4) = 6n \][/tex]

1. Distribute the constants inside the parentheses:
[tex]\[ 3n - 27 - 2n - 8 = 6n \][/tex]

2. Combine like terms on the left side:
[tex]\[ (3n - 2n) - 27 - 8 = 6n \][/tex]
[tex]\[ n - 35 = 6n \][/tex]

3. Isolate the variable [tex]\( n \)[/tex] by moving the [tex]\( n \)[/tex] term to the right side:
[tex]\[ -35 = 6n - n \][/tex]
[tex]\[ -35 = 5n \][/tex]

4. Solve for [tex]\( n \)[/tex] by dividing both sides by 5:
[tex]\[ n = \frac{-35}{5} \][/tex]
[tex]\[ n = -7 \][/tex]

So, the solution to the equation is:
[tex]\[ n = -7 \][/tex]